Inkulturasi Gereja Asia: Suatu Tinjauan Inkulturasi dalam Terang Dokumen FABC - Chrystian Loudry Malau; Tarigas Balo Raya; Yohanes Endi (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2024)
The use of the meaning of inculturation received important attention from the Asian Church in the FABC document. According to the FABC, inculturation must be translated into the spirit of the Second Vatican Council in Asian culture. However, the translation often does not match what is expected. This is because the translation was compiled differently and in another culture, so it doesn't make sense. The FABC then sought an answer to that question. First of all, FABC sees that inculturation has a theological basis. There are three foundations of inculturation: creation theology, based on the incarnation of the word and following the theology of the Church. FABC also has an interest in liturgical inculturation. First of all, the FABC emphasizes that the liturgy is a celebration of the faith and a form of evangelism. In inculturation, the liturgy must also be included. This is because the liturgy is the source and pinnacle of the Church's mission. In other words, the mission of the Church and the inculturation carried out must reach its climax in the liturgical celebration. This is because the liturgy must be the most indigenous form of inculturation.